From Bench to Bedside in Emerging Therapies for Gynecological Malignancies: A Narrative Review - Md. Safiullah Sarker PhD (Cancer Control)
Gynecological malignancies, including cervical, endometrial, and ovarian cancers, pose significant global health challenges due to their increasing incidence and limitations in conventional treatments. Current therapeutic approaches, such as surgery, chemotherapy, and radiation, often face obstacles like multidrug resistance, tumor recurrence, and adverse side effects. In response, emerging therapies—including targeted therapy, immunotherapy, and gene therapy—are reshaping treatment paradigms. Precision medicine, leveraging Poly ADP-ribose Polymerase (PARP) and Vascular Endothelial Growth Factor (VEGF) inhibitors, enhances therapeutic efficacy, while immune checkpoint inhibitors and vaccine-based therapies offer promising immunotherapeutic strategies. Additionally, advancements in nanotechnology and gene therapy, including Clustered Regularly Interspaced Short Palindromic Repeats (CRISPR) based approaches and nanoparticle-mediated drug delivery, provide novel treatment modalities. Despite these innovations, translational challenges persist, necessitating further research into clinical applications and personalized treatment strategies. This review highlights the latest advancements in emerging therapies for gynecological malignancies, emphasizing their potential to improve patient outcomes and address existing treatment limitations.